Green Preparation of Cu Nanoparticles with Bioreductor of Red Dragon Fruit Peel Extract: Visible Spectroscopy Properties - Ramadhan, La Ode Ahmad Nur; Fanihu, Siti Linda Cahayani; Watoni, Abdul Haris; Rijal, Rijal; Santoso, Nur Sofa Camelia; Rafiqa, Wa Ode Nasyarah; Haruna, Cindy Agriningsih; Arifin, Zainal Syam (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Copper nanoparticles have been successfully synthesized using the green synthesis method by utilizing red dragon fruit peel extract as a bioreductor. Red dragon fruit peel contains secondary metabolites that can reduce Cu2+ ions to Cu0. Physically, the formation of copper nanoparticles is indicated by a color change from light blue to green. In addition, the success of copper nanoparticles of red dragon fruit peel extract can be analyzed using a Visible and Fourier Transform Infrared (FTIR) spectrophotometer. The measurements using a Visible spectrophotometer showed the formation of copper nanoparticles at absorption peaks in the wavelength range of 400-450 nm. The stability of copper nanoparticles can be determined through the SPR peak absorption for 30 minutes, which shows that copper nanoparticles have good stability and have an estimated particle range of 46.43-92.93 nm, with a band gap value of 2.45 eV. The results of the FTIR spectrum on copper nanoparticles-red dragon fruit peel extract show a shift in the absorption peak of the wave number 3412.07 cm-1 to a wave number of 3439.07 cm-1 indicating a reduction of Cu2+to Cu0.